Quantification of traffic-induced compaction based on soil and agricultural implement parameters - Wang, Xianliang; Zhang, Xiangcai; Lin, Xiaona; Sha, Luming; Yang, Hanyu; Guo, Zhaoyang; Chen, Zeyu; Sun, Rongyan (International Journal of Agricultural and Biological Engineering, 2020)
Vehicle-induced soil compaction occurs when agricultural machinery is working in the fields. The accumulated soil compaction could destroy soil structure and inhibit crop growth. The low degree of visualization of soil compaction has always been an important reason for restricting the development of compaction alleviation technology. Therefore, the main objective of this study was to predict soil compaction based on soil and agricultural implement parameters. The component of soil compaction prediction includes traffic-induced stress transmission evaluation and the quantitative relationship between soil stress and bulk density. The modified FRIDA model was used to elucidate the soil stress propagation, which has been validated by previous studies. The Bailey formula was used to establish the intrinsic relationship between soil stress and bulk density. The soil uniaxial compression test was applied to obtain the parameters of the Bailey formula, and soil samples were prepared with three different levels of water content. After fitting with the Bailey formula, under the condition that the soil moisture contents were 16%, 20%, and 24%, the fitting coefficients of soil bulk density were respectively 0.980, 0.959, and 0.975, which were close to 1. The results indicated that the Bailey formula could be used to calculate soil bulk density based on the stress conditions of the soil. To verify the practicality of the soil compaction prediction model, a field experiment was carried out in Zhuozhou City, Hebei Province, China. The treatment was set for 1, 3, 5, 7, and 9 times compaction with two different loads of compaction equipment. The results showed that the fit coefficient between the predicted and measured values of soil bulk density was greater than 0.641. The slope of the equation was greater than 0.782, proving that the soil bulk density prediction model based on agricultural implements and soil parameters has a good predictive effect on soil bulk density. The soil compaction evaluation model can provide a theoretical basis to further understand the soil compaction mechanism, allowing rational measures of soil compaction alleviation to be made. Keywords: soil traffic-induced compaction, agricultural implement, soil bulk density, no-tillage, soil structure, quantification DOI: 10.25165/j.ijabe.20201305.5480 Citation: Wang X L, Zhang X C, Lin X N, Sha L M, Yang H Y, Guo Z Y, et al. Quantification of traffic-induced compaction based on soil and agricultural implement parameters. Int J Agric & Biol Eng, 2020; 13(5): 134–140.